Linaclotide inhibits colonic and urinary bladder hypersensitivity in adult female rats following unpredictable neonatal stress. Issue 10 (24th May 2018) - Ligon, C.; Mohammadi, E.; Ge, P.; Hannig, G.; Higgins, C.; Greenwood‐Van Meerveld, B.
Abstract: Background: Irritable bowel syndrome (IBS) and bladder pain syndrome (BPS) are female‐predominant, chronic functional pain disorders that are associated with early life stress (ELS) and therapeutic options for such patients remain limited. Linaclotide, a guanylate cyclase‐C (GC‐C) agonist, relieves abdominal pain and bowel symptoms in adult patients suffering from IBS with constipation. Here, we test the hypothesis that linaclotide will reverse colon and bladder hyperalgesia in a female‐specific rodent model of adverse early life experience. Methods: Neonatal rats were exposed to an odor‐attachment learning paradigm of early life stress (ELS). In adulthood, the effect of linaclotide (3 μg kg −1  d −1, p.o.) on colonic and bladder sensitivity was assessed via quantification of the visceromotor response to colorectal distension and the frequency of withdrawal responses to the application of von Frey hairs to the suprapubic region. In another cohort of rats, the effect of linaclotide on ELS‐induced colonic and bladder permeability was investigated via measurements of transepithelial electrical resistance (TEER). Key Results: Rats exposed to unpredictable ELS exhibited colonic and bladder hypersensitivity that was significantly reduced by linaclotide compared to vehicle‐treated controls. Colonic and bladder tissue isolated from adult rats exposed to unpredictable ELS exhibited a decrease in colonic and bladder TEER that was reversed by linaclotide. Conclusions and Inferences: Our results demonstrate that neonatal rats exposed to unpredictable ELS develop increased sensitivity and permeability of the colon and bladder in adulthood through a mechanism involving activation of peripheral GC‐C signaling. Abstract : Irritable bowel syndrome (IBS) and bladder pain syndrome (BPS) are female‐predominant, chronic functional pain disorders that are associated with early life stress (ELS) and therapeutic options for such patients remain limited. In this study, we test the hypothesis that linaclotide will reverse colon and bladder hyperalgesia in a female‐specific rodent model of adverse early life experience and found rats exposed to unpredictable ELS exhibited colonic and bladder hypersensitivity as well as enhanced permeability that was reversed by linaclotide.